A Systematic Approach to Strategy Formulation for Medium-Sized Shipyards - Ma'ruf, Buana (SBM ITB, 2007)
A more comprehensive strategy formulation has an important role for sustainable competitive advantage of the shipbuilding companies in the global market. The nature of shipbuilding industry differs from general industry, therefore a strategy formulation model should be developed based on its own characteristics and business environment. This paper presents a proposed strategy formulation model for medium-sized shipyards both in business and corporate levels. A new approach was developed based on comprehensive business environment analysis, using questionnaires to the industry's stakeholders and multivariate analysis 'Factor Analysis.' From the analysis, two business environmental models are made, and combined into corporate model called 'Ten-boundary environment model.' These models are used to develop Shipyard Matrix, then integrated into a shipyard strategy formulation model, called 'YARDSTRAT,' using the David's strategy formulation framework. Real case application and discussion have been carried out in two national shipyards. The proposed model and the results were compared to their existing formulation model for model evaluation and validation, using 12 evaluation criteria. The results show that, the average value of each criteria of the proposed model is much higher than the average value of the existing model (SWOT analysis).Â Key words: shipyard, environment model, strategy formulation, strategic management